High-temperature-resistant high-strength high-entropy alloy and additive manufacturing method thereof

By preparing a high-entropy alloy with specific components and using electron beam selection melting technology for additive manufacturing, the problems of high-entropy alloy powder splashing and low density are solved, high density and excellent high-temperature mechanical properties are achieved, and the industrial application potential of the alloy is enhanced.

CN119566328APending Publication Date: 2025-03-07GRIMAT ENG INST CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411634728.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

When the existing electron beam additive manufacturing technology prepares high-entropy alloys, the powder splashes severely and has low density. The traditional smelting process has many casting defects, difficulty in preparing large-sized billets, and difficulty in plastic processing, which limits the industrial application of high-entropy alloys.

Method used

Using a high temperature resistant high strength and high entropy alloy, its components include Ni, Fe, Co, Cr, Al, Ti, B and Nb, additive manufacturing is made by electron beam selection melting technology. The specific steps include magnetic levitation induction furnace smelting, aerosolization equipment preparation of powder, electron beam forming, annealing treatment and solid solution aging treatment.

Benefits of technology

The high density, excellent high temperature mechanical properties and oxidation resistance of high entropy alloys are achieved, which solves the problems of powder splashing and low density, and improves the industrial application potential of the alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119566328A_ABST
    Figure CN119566328A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of metal structure materials, in particular to a high-temperature-resistant high-strength high-entropy alloy and an additive manufacturing method thereof. The alloy comprises the following components: 15 at%-16.5 at% of Ni, 35 at%-45 at% of Fe, 15 at%-17.5 at% of Co, 15 at%-25 at% of Cr, 1 at%-1.5 at% of Al, 4 at%-6 at% of Ti, 0.2 at%-0.5 at% of B and 0.2 at%-0.5 at% of Nb, the alloy is prepared by an additive manufacturing method, and by regulating and controlling the process conditions of powder granularity, electron beam parameters, preheating of a substrate, preheating of powder and the like, the thickness of the alloy can be adjusted and controlled, and the thickness of the alloy can be adjusted and controlled. The high-temperature-resistant, high-strength and high-entropy alloy composed of a body-centered cubic (FCC) phase matrix, a micron L21 phase, a Ni3Al nano precipitated phase (gamma) and a body-centered cubic (BCC) phase is obtained, and the high-temperature mechanical property, compactness and other physical properties of the alloy can be greatly improved. The high-entropy alloy component formed through electron beam additive manufacturing overcomes the defects that high-entropy alloy prepared through a traditional method has many defects, the cost is high, and the forming period is long, and the good application prospect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metal structural materials, and in particular to a high-temperature resistant high-strength high-entropy alloy and an additive manufacturing method thereof. Background Art

[0002] With the rapid development of aviation, aerospace, nuclear industry, automobile, chemical industry and other fields, higher requirements are put forward for high temperature performance and lightweight of turbine discs, cladding, heat exchangers, tail nozzles and other components. In the existing technology, nickel-based and cobalt-based high-temperature alloys are the most widely used high-temperature materials for temperatures above 650°C, but they have high density (>8g / cm 3 ), and the long-term use temperature of most systems is difficult to exceed 1100℃. At present, the materials that are expected to replace traditional nickel-based and cobalt-based high-temperature alloys are mainly: Nb-Si-based high-temperature alloys, CC-based composite materials, ceramic materials and platinum group metals. However, the problem of poor high-temperature oxidation resistance of Nb-Si-based high-temperature alloys and CC-based composite materials has not been solved; ceramic materials are brittle and have poor processing performance; platinum group metals are expensive and have high density. It can be seen that it is necessary to design and develop new high-temperature resistant, lightweight, high-performance new materials that can be used at temperatures above 650℃.

[0003] As an emerging multi-principal alloy material, high-entropy alloy (HEA) has a broad composition design space, and its unique structure gives it excellent comprehensive properties. The most studied high-entropy alloys are 3d transition series high-entropy alloys (TM HEAs) and refractory series high-entropy alloys (RHEAs). 3d transition series high-entropy alloys are composed of transition elements such as Fe, Cr, and Co. Among them, 3d transition series high-entropy alloys with face-centered cubic phase (FCC), body-centered cubic phase (BCC) and nanoprecipitation phase have excellent comprehensive properties and become ideal materials that can be used at 650-1100℃ to replace traditional high-temperature alloys.

[0004] However, with the rapid and high-quality development of modern industry, the performance requirements of high-entropy alloys for complex hot-end components in high thrust-to-weight ratio engines and high-temperature nuclear reactors are becoming more and more stringent. At present, the method for preparing FeCrCo 3d transition family high-entropy alloys is mainly arc melting (induction melting) + mechanical processing. The traditional smelting process for preparing high-entropy alloys has many casting defects, large-size billets are difficult to prepare, plastic processing is difficult, the process is complicated, the alloy structure is uneven, and there is a lot of material waste, which to a certain extent limits the industrial application of high-entropy alloys.

[0005] Selective electron beam melting (SEBM) technology, also known as additive manufacturing technology, has opened up a new path for the development and production of complex high-entropy alloy parts. Compared with traditional alloy manufacturing processes, the SEBM technology forming process does not require molds and embryos. It can directly generate blocks of specified shapes by layer-by-layer accumulation according to the designed model data. It can quickly, accurately and efficiently manufacture parts with any complex external and internal shapes, thereby realizing "design is what you get", realizing free and personalized manufacturing, and greatly reducing the processing steps and shortening the processing cycle from a technical level. When preparing high-entropy alloys using electron beam selective melting technology, the electron beam power is often low (100-200W). For example, this process parameter is applicable to the high-entropy alloy manufacturing in Chinese patents CN118222901A and CN115058626B. However, scanning at a low power will cause incomplete melting. Increasing the electron beam power will cause serious splashing of the powder, resulting in problems such as low alloy density. Summary of the invention

[0006] Therefore, in order to solve the problems of severe splashing of high entropy alloy powder, low density of components, high temperature resistance, strength, and light weight of high entropy alloys prepared by existing electron beam additive manufacturing technology, this patent provides a high-temperature resistant and high-strength high entropy alloy and its additive manufacturing method.

[0007] A high temperature resistant high strength high entropy alloy, the composition of which is Ni: 15at%-16.5at%, Fe: 35at%-45at%, Co: 15at%-17.5at%, Cr: 15at%-25at%, Al: 1at%-1.5at%, Ti: 4at%-6at%, B: 0.2at%-0.5at%, Nb: 0.2at%-0.5at%, the microstructure of the high temperature resistant high strength high entropy alloy is composed of a face-centered cubic phase FCC matrix, a micron-sized L21 phase, a Ni3Al nano-precipitated phase γ` and a body-centered cubic BCC phase, the density of the high temperature resistant high strength high entropy alloy is greater than 90%, and the density is less than 7.8g / cm 3 .

[0008] An additive manufacturing method for the above alloy, selecting a metal with a purity higher than 99.5% as an alloy raw material, the alloy raw material composition ratio is: Ni: 15at%-16.5at%, Fe: 35at%-45at%, Co: 15at%-17.5at%, Cr: 15at%-25at%, Al: 1at%-1.5at%, Ti: 4at%-6at%, B: 0.2at%-0.5at%, Nb: 0.2at%-0.5at%, the preparation method steps are:

[0009] Step 1: placing the alloy raw material in a magnetic levitation induction furnace for smelting, and after the alloy raw material is completely melted into a liquid state, maintaining the smelting for 2 minutes to 5 minutes, and obtaining an alloy ingot after cooling; turning the alloy ingot over and repeating the smelting process, and the number of repetitions of the turning-melting is not less than 2 times, to obtain a high-temperature high-entropy alloy ingot;

[0010] Step 2: placing the high temperature high entropy alloy ingot in a gas atomization device to prepare a high entropy alloy powder, wherein the powder particle size distribution range is 60-80 μm and the average particle size is 70-75 μm;

[0011] Step 3: Place the substrate on the forming platform in the forming chamber of the additive manufacturing device and level it. The substrate is surrounded by high entropy alloy powder. The electron gun and the forming chamber of the device are evacuated to a vacuum degree of less than 1×10 -2 After that, high-purity inert gas was filled in until the vacuum degree was 1×10 -1 -2×10 -1 Pa;

[0012] Step 4: Import the three-dimensional model stl file of the preformed alloy into the computer, automatically layer it using MetaBuild 1.0 software, set the working parameters and scanning mode of the electron beam, the working parameters of the electron beam are current 10-20mA, scanning speed 3-10m / s, and the scanning mode is serpentine scanning;

[0013] Step 5: preheating the substrate to a set temperature, then spreading the first layer of the high entropy alloy powder on the surface of the substrate and performing powder selective melting by electron beam serpentine scanning, and then completing the two processes of powder preheating and powder selective melting for each layer of high entropy alloy powder until the alloy component is completed. The preheating temperature of the substrate preheating or powder preheating is 850-950°C, and the power of powder selective melting is set to 2.9-3.2kW;

[0014] Step 6: After vacuum sealing the alloy component, annealing and solution aging treatment are performed in sequence to obtain a high-temperature resistant, high-strength, high-entropy alloy, wherein the annealing temperature is 600°C-800°C, the annealing time is 12-20h, the solution temperature is 900°C-1200°C, the solution time is 2-6h, the aging temperature is 710-800°C, and the aging time is 12-20h.

[0015] Furthermore, before the step 1 is performed, the alloy raw material is firstly polished and then ultrasonically cleaned in industrial-grade ethanol for 20 min-25 min.

[0016] Furthermore, in step 1, the magnetic suspension induction furnace is evacuated to a vacuum degree of 3×10 -3 Pa-5×10 -3Pa, and then fill the magnetic levitation induction furnace with protective gas to keep the pressure at 5×10 -3 MPa-1×10 -2 MPa, the protective gas is a high-purity inert gas; during the smelting process, the arc starting current is 150A-250A, and the smelting current is 300A-450A.

[0017] Furthermore, the vacuum degree of the gas atomization equipment in step 2 during the preparation of high entropy alloy powder is 3×10 - 3 Pa-5×10 -3 Pa.

[0018] Furthermore, the high-purity inert gas in step 1 and / or step 3 is He gas.

[0019] Furthermore, the operating parameters of the electron beam in step 4 are preferably: current 12-18 mA, scanning speed 4-8 m / s.

[0020] Furthermore, it is preferred that the annealing treatment temperature of step 6 is 600°C-800°C, the annealing time is 18 hours, the solid solution temperature is 900°C-1100°C, the solid solution time is 3-6 hours, the aging temperature is 710-800°C, and the aging time is 14-18 hours.

[0021] The beneficial effects of the preparation method and the prepared alloy of the present invention are:

[0022] (1) The high entropy alloy of the present invention has the advantages of high temperature resistance, high strength, high density, and oxidation resistance. Among them, in the matching of element ratios, the cracking sensitivity is reduced by reducing the Al element, and a trace amount of B element is added to the alloy to form borides at the grain boundary position, pin the grain boundary, and improve the grain boundary bonding strength. However, the boron element also has side effects. For example, the enrichment of boron elements at the grain boundary position will promote grain boundary liquefaction and increase the cracking sensitivity. Therefore, in the present invention, an appropriate amount of B element is added to improve the strength of the alloy while avoiding the cracking of the alloy. Adding a small amount of Nb element can reduce the crack sensitivity and further prevent cracking; the Fe element content in the alloy is relatively high, which avoids the alloy powder from splashing during the electron beam construction process. On the one hand, it can improve the density of the component, and on the other hand, it can improve the efficiency of electron beam printing. In addition, an appropriate amount of anti-oxidation Al element and Cr element are added to the alloy, and a high temperature environment can form a dense Al2O3 and Cr2O3 oxide film on the outside of the alloy, which plays a role in preventing the diffusion of oxygen elements and improving the high temperature oxidation resistance of the alloy.

[0023] (2) The high entropy alloy prepared by the method of the present invention is composed of FCC (body-centered cubic) phase (γ) matrix, micron L21 phase, Ni3Al nanoprecipitate phase (γ`) and BCC phase. Ni3Al nanoprecipitate phase (γ`) and L21 phase can greatly improve the high temperature mechanical properties of the alloy, and the body-centered cubic BCC phase can further improve the strength of the alloy. Under room temperature tensile environment, the tensile strength of the alloy is not less than 840MPa, the yield strength is not less than 440MPa, and the elongation is not less than 4%; under 650℃, the tensile strength of the alloy is not less than 640MPa, the yield strength is not less than 210MPa, and the elongation is not less than 17%, which has excellent comprehensive performance.

[0024] (3) The present invention uses electron beam selective melting technology, i.e., additive manufacturing technology, to prepare high entropy alloys, which makes up for the problem of many internal defects in alloys prepared by traditional smelting methods and improves the comprehensive performance of the alloys. In the smelting process, the alloy raw materials are fully smelted through the flipping-smelting process of the ingot, which is conducive to the formation of various phases of the high entropy alloy and the improvement of properties such as density; in the process of preparing the powder, particles with a particle size of 60-80 μm are prepared. This particle size is combined with the high-speed serpentine scanning strategy and specific current of the subsequent electron beam selective melting, which can make the alloy powder heated more evenly and fully, fully melted, and make the component density higher and the comprehensive mechanical properties better; the introduction of He gas during the electron beam selective melting process and the appropriate increase in the Fe element content in the powder can avoid powder splashing during the electron beam construction process; at the same time, before the selective melting, the substrate and each layer of powder are preheated, and each layer of powder is also preheated by heating the substrate, and the preheating temperature is 600℃-8 00℃, the theoretical temperature of the electron beam at a power of 2.9-3.2kW is about 1600℃. The preheating operation of the substrate can prevent the first layer of powder from being disintegrated by the charge repulsion under the high-energy electron beam, causing each layer of the subsequent powder to be uneven, thereby leading to uneven heating during the electron beam selective melting process. The preheating operation of each layer of powder can effectively reduce the temperature gradient between the upper and lower layers, making the microstructure and phase distribution of the alloy component more uniform; at the same time, the final annealing treatment and solid solution aging treatment further improve the uniformity and mechanical properties of the alloy structure, and through the solid solution aging treatment, the dispersed Ni3Al nanoprecipitation phase (γ`) and L21 phase are generated in the alloy, which can greatly improve the high-temperature mechanical properties of the alloy, and the body-centered cubic BCC phase can further improve the strength of the alloy.

[0025] (4) The present invention can prepare high-temperature resistant, high-strength, high-entropy alloy components with complex shapes through electron beam additive manufacturing technology, which makes up for the problem of long process and high cost in preparing complex components with traditional machining technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The embodiments of the present invention are further described below with reference to the accompanying drawings, in which:

[0027] Figure 1 shows the SEM image of the alloy of Example 4;

[0028] Figure 2 The 650°C compression performance diagram of the alloy of Example 4 is shown;

[0029] Figure 3 The 950°C compression performance diagram of the alloy of Example 4 is shown;

[0030] Figure 4 The XRD pattern of the alloy of Example 4 is shown;

[0031] Figure 5 The microstructure morphology of the alloy of Example 4 is shown;

[0032] Figure 6 The projection analysis diagram of the Example 4 alloy is shown. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below through specific embodiments in conjunction with the accompanying drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0034] The preparation methods of Examples 1 to 10 are as follows:

[0035] Raw material configuration: Fe, Co, Cr, Ni, Al, Ti, B, and Nb with a purity higher than 99.5% were selected as metallurgical raw materials. The oxide surface of the metallurgical raw materials was polished with sandpaper, and ultrasonically cleaned in industrial-grade ethanol for 20 minutes. After drying, the raw material components were weighed according to the atomic fraction.

[0036] Step 1: Place the raw materials in a magnetic levitation induction furnace and evacuate to a vacuum degree of 4×10 -3 After the furnace is filled with high-purity He gas, the pressure inside the furnace is maintained at 1×10 -2 MPa, alloy melting is performed on the raw materials in the magnetic suspension induction furnace, the arc starting current is 200A, the melting current is 450A, and after the raw materials in the copper crucible are completely melted into liquid, the melting is maintained for 5 minutes, and the alloy ingot is obtained after cooling, and the alloy ingot is turned over and the melting process is repeated. The number of times of turning over and melting is repeated is 2-4 times, and a high-temperature high-entropy alloy ingot is obtained;

[0037] Step 2: Place the high entropy alloy ingot in the gas atomization equipment and then evacuate to a vacuum degree of 3×10 -3 After Pa, high entropy alloy powder was prepared, and the powder particle size distribution range was 60-80μm;

[0038] Step 3: Place the substrate in the forming platform and level it. Surround the substrate with high entropy alloy powder to reduce the temperature gradient. Evacuate the electron gun and forming chamber of the equipment to a vacuum degree of less than 1×10 -2 After the vacuum is 1.5×10 -1 Pa, can prevent powder from splashing;

[0039] Step 4: Import the 3D model stl file of the preformed part into the computer, use MetaBuild 1.0 software to automatically layer it, and set the forming process parameters and serpentine scanning method;

[0040] Step 5: Before forming, the substrate is preheated. After the substrate is preheated, the first layer of powder is spread on its surface, and the powder is melted in a serpentine scanning strategy. After that, the two processes of powder preheating and powder melting are completed in sequence for each layer of powder. When the electron beam completes the forming of the current layer of powder, the forming table drops the height of one layer of powder and lays a new layer of powder on the forming surface. This process of layer-by-layer powder laying, preheating, and scanning is repeated until the part is built.

[0041] Step 6: The sample is sealed and placed in a heat treatment furnace for annealing and solution aging treatment.

[0042] Table 1 Alloy raw material ratios of the embodiments and comparative examples

[0043]

[0044]

[0045] Table 2 Method parameters of Examples and Comparative Examples

[0046]

[0047] The above preparation method is used to prepare a high temperature resistant, high strength and high entropy alloy composed of FCC (body centered cubic) phase (γ) matrix, micron L21 phase, Ni3Al nanoprecipitate phase (γ`) and BCC phase, and a dense oxide film is formed on the surface of the alloy, which is resistant to oxidation. Figure 1 As shown, other mechanical properties of the alloy were uniformly tested.

[0048] Table 3 Performance parameters of the embodiments and comparative examples

[0049]

[0050]

[0051] It can be seen from Table 3 that the alloys prepared according to the alloy composition ratio and process parameters of this solution have better mechanical properties at room temperature and high temperature (650° C.) than the comparative example, among which Example 4 has the best effect. Figure 3 and Figure 4 The compression strengths of Example 4 at 650°C and 950°C are respectively: at 650°C, the compression amount is 50%, and the compression strength of Example 4 is 970MPa; at 950°C, the compression amount is 50%, and the compression strength of Example 4 is 550MPa. The compression strengths at room temperature and 650°C are better than those of Comparative Examples 1-4.

[0052] Figure 4 This is the XRD spectrum of the high entropy alloy of Example 4. As can be seen from the figure, the alloy phase is composed of BCC+FCC+γ` three phases. The main crystal planes are (111), (200), (211), (220), (221).

[0053] Figure 5 The microstructure morphology of Example 4. The alloy consists of two phases of BCC+FCC solid solution, in which fine needle-shaped BCC phase (black contrast) is evenly distributed in the FCC solid solution matrix (white contrast). The BCC phase content is relatively small. The main reason is that compared with the traditional vacuum melting process, SEBM belongs to a rapid solidification process, so the extremely high cooling rate can significantly inhibit the precipitation of the BCC phase. However, in the SEBM forming process, the electron beam quickly preheats the powder layer with a high-energy electron beam before forming, and the heat diffuses up and down. The alloy undergoes thermal cycling during the SEBM forming process, which causes the BCC phase to precipitate from the FCC phase.

[0054] In order to further analyze the alloy structure, TEM analysis was performed on the alloy of Example 4. The results are as follows Figure 6 As shown. The transmission image clearly shows two different phases, namely the FCC phase and the needle-shaped L21 phase. Through the diffraction spot analysis, the FCC phase is composed of two sets of diffraction spots, namely the strong diffraction spot FCC and the weak diffraction spot γ` phase.

[0055] Some exemplary embodiments of the present invention are described above. It can be understood that the above embodiments are only used to explain the present invention and do not constitute a limitation on the protection scope of the present invention. The features in these embodiments can be recombined in a suitable manner, and the scheme obtained thereby is still within the protection scope required by the present invention. Based on the above embodiments, all other embodiments obtained by those skilled in the art without making creative work, that is, all modifications, equivalent substitutions and improvements made within the spirit and principles of this application, fall within the protection scope required by the present invention.

Claims

1. A method for additive manufacturing of a high temperature resistant, high strength and high entropy alloy, characterized in that: A metal with a purity higher than 99.5% is selected as an alloy raw material, and the composition ratio of the alloy raw material is: Ni: 15at%-16.5at%, Fe: 35at%-45at%, Co: 15at%-17.5at%, Cr: 15at%-25at%, Al: 1at%-1.5at%, Ti: 4at%-6at%, B: 0.2at%-0.5at%, Nb: 0.2at%-0.5at%, and the preparation method steps are as follows: Step 1: placing the alloy raw material in a magnetic levitation induction furnace for smelting, and after the alloy raw material is completely melted into a liquid state, maintaining the smelting for 2 minutes to 5 minutes, and obtaining an alloy ingot after cooling; turning the alloy ingot over and repeating the smelting process, and the number of repetitions of the turning-melting is not less than 2 times, to obtain a high-temperature high-entropy alloy ingot; Step 2: placing the high temperature high entropy alloy ingot in a gas atomization device to prepare a high entropy alloy powder, wherein the powder particle size distribution range is 60-80 μm and the average particle size is 70-75 μm; Step 3: Place the substrate on the forming platform in the forming chamber of the additive manufacturing device and level it. The substrate is surrounded by high entropy alloy powder. The electron gun and the forming chamber of the device are evacuated to a vacuum degree of less than 1×10 -2 After that, high-purity inert gas was filled in until the vacuum degree was 1×10 -1 -2×10 -1 Pa; Step 4: Import the 3D model file of the preformed alloy into the computer, automatically layer it using software, and set the working parameters and scanning mode of the electron beam. The working parameters of the electron beam are current 10-20mA, scanning speed 3-10m / s, and serpentine scanning; Step 5: preheating the substrate to a set temperature, then spreading the first layer of the high entropy alloy powder on the surface of the substrate and performing powder selective melting by electron beam serpentine scanning, and then completing the two processes of powder preheating and powder selective melting for each layer of high entropy alloy powder until the alloy component is completed. The preheating temperature of the substrate preheating or powder preheating is 850-950°C, and the power of powder selective melting is set to 2.9-3.2kW; Step 6: After vacuum sealing the alloy component, annealing and solution aging treatment are performed in sequence to obtain a high-temperature resistant, high-strength, high-entropy alloy, wherein the annealing temperature is 600°C-800°C, the annealing time is 12-20h, the solution temperature is 900°C-1200°C, the solution time is 2-6h, the aging temperature is 710-800°C, and the aging time is 12-20h.

2. The method according to claim 1, characterized in that Before the step 1, the alloy raw material is firstly polished and then ultrasonically cleaned in industrial-grade ethanol for 20-25 minutes.

3. The method according to claim 1, characterized in that In step 1, the magnetic levitation induction furnace is evacuated to a vacuum degree of 3×10 -3 Pa-5×10 -3 Pa, and then fill the magnetic levitation induction furnace with protective gas to keep the pressure at 5×10 -3 MPa-1×10 -2 MPa, the protective gas is a high-purity inert gas; during the smelting process, the arc starting current is 150A-250A, and the smelting current is 300A-450A.

4. The method according to claim 1, characterized in that: The vacuum degree of the gas atomization equipment in step 2 during the preparation of high entropy alloy powder is 3×10 -3 Pa-5×10 -3 Pa.

5. The method according to any one of claims 1 or 3, characterized in that: The high-purity inert gas in step 1 and / or step 3 is He gas.

6. The method according to claim 1, characterized in that The operating parameters of the electron beam in step 4 are: current 12-18 mA, scanning speed 4-8 m / s.

7. The method according to claim 1, characterized in that The annealing treatment temperature of step 6 is 600°C-800°C, the annealing time is 18 hours, the solid solution temperature is 900°C-1100°C, the solid solution time is 3-6 hours, the aging temperature is 710-800°C, and the aging time is 14-18 hours.

8. A high temperature resistant, high strength and high entropy alloy, characterized in that: The composition is Ni: 15at%-16.5at%, Fe: 35at%-45at%, Co: 15at%-17.5at%, Cr: 15at%-25at%, Al: 1at%-1.5at%, Ti: 4at%-6at%, B: 0.2at%-0.5at%, Nb: 0.2at%-0.5at%, the microstructure of the high temperature resistant high strength high entropy alloy is composed of a face-centered cubic phase FCC matrix, a micron-sized L21 phase, a Ni3Al nano-precipitated phase γ` and a body-centered cubic BCC phase, the density of the high temperature resistant high strength high entropy alloy is greater than 90%, and the density is less than 7.8g / cm 3 .

Citation Information

Patent Citations

  • High entropy alloy member, method for producing alloy member, and product using alloy member

    CN108431262A

  • Method for preparing high-density, high-toughness and high-entropy alloy through selective electron beam melting technology

    CN114192800A

  • High-entropy alloy foam structure multi-electron beam additive manufacturing method

    CN114850494A

  • Dispersion-strengthened high-strength high-temperature high-entropy alloy and preparation method thereof

    CN114892063A

  • Preparation method for improving density of AlxCoCrFeNi series high-entropy alloy

    CN116426783A